HBR guides to building your strategic skills collection 3 books - Harvard Business Review Press; Recorded Books, Inc. (Boston, MA : Harvard Business Review Press, 2020)
If you aren't working with a strategy, you're wasting your time. Strategy isn't just a set of plans handed down from the C-suite. To grow as a leader, you need to understand your company's strategy and align your thinking, projects, and team with organizational goals and vision. Master these abilities with the HBR Guides to Building Your Strategic Skills Collection. This three-book set, which includes the HBR Guide to Thinking Strategically, the HBR Guide to Managing Strategic Initiatives, and the HBR Guide to Setting Your Strategy, will help you change the way you think about your work, manage your most important priorities, and craft a strategy for long-term growth. You'll learn how to: -Understand what strategy is--and what it isn't -Define a clear strategy, whether you're in a start-up or in an established business -Manage a portfolio of strategic projects -Embed strategic thinking into your daily tasks and decision making -Align your team around key objectives -Let go of work that doesn't add value -Communicate strategy throughout your organization Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.
HBR guide to setting your strategy -- HBR guide to managing strategic initiatives -- HBR guide to thinking strategically.
Title from resource description page (Recorded Books, viewed August 10, 2020).
Master record variable field(s) change: 050, 082, 650
Keywords: BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Strategic planning; Business planning; Project management; Success in business; Business; elektronické knihy; electronic books